GAIA : uma proposta de guia de recomendações de acessibilidade web com foco em aspectos do autismo - Britto, Talita Cristina Pagani (Universidade Federal de São Carlos, 2016)
In the past 20 years, computer solutions has been used as a support tool for children with Autism Spectrum Disorder (ASD), as well for their parents, therapists and educators. Those solutions may be helpful to work social skill, memorizing, communication, vocabulary acquisition, literacy, and other aspects. However, there is lack of artifacts to guide software designers to plan and implement computer solutions suitable to the needs of children with ASD. The literature provide some considerations regarding this factor, but many of them are understandable only for education or computer professionals exclusively. Besides, many contributions may have a restrict access due to paywalls. Those factors motivated the development of GAIA (Guidelines for Accessible Interfaces for people with Autism), a set of 28 guidelines intend to help software developers and digital educators to better understand how to develop website that are suitable to the needs of children with Autism. To develop GAIA, this research was conducted in three stages: a) exploratory bibliographic survey, which generated the first version of the guidelines of GAIA; b) Application of an online survey to map the knowledge of web developers regarding cognitive, neuronal or learning disabilities, in order to understand their gap of knowledge; c) interviews with parents of children with ASD to understand empathically the social, therapeutic and pedagogic value of the technology for children with ASD. Triangulating the data from the three stages, it was possible to get the following conclusions: (i) developers have difficult in understanding the existing materials about web accessibility and also have a lack of knowledge about cognitive disabilities; (ii) the interviews made possible to understand in depth the context of use of the technology by children with ASD; (iii) there were recurring interaction aspects in the interviews that were not found in the literature. With those results, it was possible to refine the guidelines of GAIA e make them available through a website hosted in an open-source repository, so they can be easily accessible by people.
Keywords: Autismo; Acessibilidade web; Design inclusivo; Recomendações de design; Autism; Web accessibility; Inclusive design; Design guidelines; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO